1. SOME FACTORS RELATED TO SMALL LIVER FLUKE INFECTION IN YEN BINH DISTRICT, YEN BAI PROVINCE (Vietnam Journal of Community Medicine, 2025)
Objective: Identify some factors related to small liver fluke infection in human in Yen Binh district, Yen Bai province in 2020.Research method: Cross-sectional descriptive study were conducted to determined the rate of human infection with small liver fluke by Kato-Katz method and interview for 775 study participants with a set of questions to assess understanding, knowledge, attitudes, and practices related to small liver fluke infection and prevention.Results: The rate of liver fluke infection in this study was 45.9%, the infection rate in men were 65.1%, in women  were 32.2%. The rate of small liver fluke infection in men was higher 3.9 times than that in women (OR = 3.9; 95%CI: 2.91 - 5.33). The ethnic minorities have risk of liver fluke infection 3.5 times higher than that of Kinh people (OR = 3.5; 95%CI: 2.4 - 5.15). The age group from 30-50 years old has a 2.2 times higher risk of liver fluke infection than that in the group > 50 years old (OR = 2.2; 95%CI: 1.63-3.03). Groups < 30 years old have a 2.5 times higher risk of liver fluke infection than that in groups > 50 years old (OR = 2.5; 95%CI: 1.5-4.2). Families that own dogs and cats were higher 2 times infected with small liver flukes than that in the families that do not (OR = 2.0; 95%CI: 1.16 - 3.32).Conclusion: The rate of small liver fluke infection in men was higher 3.9 times than that in women. The factors related to small liver fluke infection include gender, ethnicity, age group, dog and cat ownership, and eating raw fish.
Keywords: related factors; small liver fluke infection; Yen Binh; Yen Bai